Examining the Effectiveness of Genetic Counselors' Communication of Variant of Uncertain Significance Results of Breast Cancer Genes. Issue 5 (16th April 2021) - Zhong, Lingzi; Donovan, Erin E.; Vangelisti, Anita L.
ABSTRACT: Receiving a variant of uncertain significance (VUS) result is quite common for individuals who undergo genetic testing. Because VUS results are often unexpected and necessarily complex, they are challenging for genetic counselors to deliver. The current research sought to examine how three specific message features (risk estimate formats, establishment of a future plan, and linguistic agency), and message receivers' intolerance of uncertainty, influenced the effectiveness of genetic counselors' communication of a VUS result. A series of MANCOVAs and multiple regressions suggested that these message features affected message receivers' perception of a genetic counselor's credibility and receivers' uncertainty appraisal and information-seeking intentions. Specifically, establishing a future plan and assigning agency to a VUS result enhanced perceived counselor credibility. When results were presented in a numeric format, assigning agency to counselors resulted in heightened danger appraisal and greater information-seeking intentions. Individuals' intolerance of uncertainty moderated the association between risk formats and uncertainty appraisal. These results have both theoretical and practical implications for communication of uncertainty in the context of genetic counseling.